A randomized, double-blind, double-dummy, multicenter trial comparing the efficacy and safety of extended- and immediate-release levetiracetam in people with partial epilepsy. (November 2018) - Wu, Tony; Lim, Siew-Na; Tsai, Jing-Jane; Chuang, Yao-Chung; Huang, Chin-Wei; Lin, Chun-Chieh; Hsu, Chang-Hung; Fung, Hong-Chung; Lee, Chih-Hong
Highlights: LEV-ER is equivalent in reducing the frequency of partial onset seizures to LEV-IR. LEV-ER add-on therapy can be well-tolerated in patients with uncontrolled epilepsy. Most of the adverse events related to LEV-ER were mild in severity, and resolved. The overall quality of life was significantly improved in the LEV-ER group. Abstract: Purpose: The aim of this trial was to compare the efficacy and safety of two formulations of levetiracetam in people with partial epilepsy over a 12-week treatment period. Methods: We performed a randomized, paralleled, and multicenter trial that consisted of a 4-week single-blind placebo run-in, followed by a 12-week double-blind, double-dummy treatment phase to compare the efficacy and safety of levetiracetam extended-release (LEV-ER) and immediate-release (LEV-IR) tablets as an adjunctive treatment in adult patients with uncontrolled epilepsy. Results: The median partial-onset seizure (POS) frequency per week (min-max) was 0.3 (0.0, 17.4; 95% confidence interval [95% CI] 1.3, 4.8) in the LEV-ER group and 0.3 (0.0, 31.4; 95% CI − 0.1, 4.3) in the LEV-IR group. No serious adverse events occurred during the trial period. Both groups had the same responder rate (58.6%), while a higher rate of seizure freedom over the treatment period was noted in the LEV-ER group compared with the LEV-IR group (27.6% vs. 13.8%, respectively). The European Quality of Life–5 Dimensions scores significantly increased in the LEV-ER–treated group, in contrast to the scores in the LEV-IR group, which decreased (7.2 vs. − 1.5, p = 0.03). Conclusion: These results suggest that LEV-ER is equivalent to LEV-IR in reducing the frequency of POS and has a similar tolerability as LEV-IR as an add-on therapy. In addition, LEV-ER treatment improved the health-related quality of life of people with uncontrolled partial epilepsy.